Effect of two succesive check dams on debris flow deposition - Maricar, Farouk; Hashimoto, Haruyuki; Ikematsu, Shinya; Miyoshi, Tomohiro (Italian journal of engineering geology and environment, 2011)
This paper describes the effect of two successive check dams on the debris flow event which occurred on 21 July, 2009 in Hofu City, Yamaguchi Prefecture, Ja- pan. The debris flow event caused sediment deposition in the check dams in the Tsurugi and Hachimandani River. In the former river with two successive closed- check dams, driftwood did not accumulate in the check dams but in the central region of the river bend. In the latter river with two successive open-check dams, driftwood accumulated in the opening of the check dams so that the accumulation obstructed the sediment transport to the downstream direction. The upstream check dams in these rivers have sediment deposition profile of around 2°, whereas the downstream ones have deposition profile of around 1.3°. The ratio of sediment deposition volume in the downstream check dams to that in the upstream ones is 0.3 : 1. The total amount of sediments trapped by the two successive check dams can be estimated at around 9,500 m3 in each river. Specific sediment runoff volume from the mountainous areas is qs = 6,800 (m3/km2).